Removal of Acid Red 88 Using Activated Carbon Produced from Pomelo Peels by KOH Activation: Orthogonal Experiment, Isotherm, and Kinetic Studies - Zheng Liu; Konglong Xing (Journal of Chemistry)
Activated carbon (PPAC) from pomelo peels was prepared by carbonization and KOH activation. The performance of PPAC was assessed by removing acid red 88 (AR88) in aqueous solution. The most suitable activation processes were found by orthogonal experiments, aimed to achieve the maximum of removal capacity of AR88. Moreover, the possible mechanisms of adsorption were studied through the results of characterization, isotherm fitting, and kinetics simulation. Results showed the preparation parameter that mattered the most to AR88 removal efficiency was the activation temperature of PPAC, followed by impregnation ratio and activation time. The optimal preparation conditions of PPAC were at activation temperature 800°C, activation time 90 min, and impregnation ratio 2.5 : 1. The characterization results showed optimal PPAC had a microporous and amorphous carbon structure whose BET specific area and total pore volume were 2504 m2/g and 1.185 cm3/g, respectively. The isotherm fitting demonstrated that the sorption process followed the Langmuir model, and theoretical maximal sorption value was 1486 mg/g. The kinetics simulation showed that the pseudo-second-order model described the sorption behavior better, suggesting chemisorption seemed to be the rate-limiting step in the adsorption process. This work presented that PPAC was a promising and efficient adsorbent for AR88 from water.